ATMOSPHERIC CIRCULATION IN THE NORTHERN HEMISPHERE AND THE ARCTIC OS-CILLATION - ХОЛОПЦЕВ, О. В.; Нікіфорова, М. П. (Харківський національний університет імені В.Н.Каразіна, 2015)
The conditions under which the statistical relationships interannual change in the total duration of the period prevalence in the northern hemisphere elementary circulation mechanisms regarding classification BL Dzerdievskogo groups meridional North and South meridional, with variations of the state of the Arctic oscillation, are significant. It is shown that in the contemporary period, changes in the characteristics of these connections may be due to changes in the distribution of surface temperature of the oceans. Выявлены условия, при которых статистические связи межгодовых изменений суммарных продолжительностей периодов преобладания в Северном полушарии Земли Элементарных Циркуляционных Механизмов, относящихся по классификации Б. Л. Дзердиевского к группам Меридиональной Северной и Меридиональной Южной, с вариациями состояния Арктической осцилляции, являются значимыми. Показано, что происходящие в современном периоде изменения характеристик этих связей могут быть обусловлены изменениями распределения поверхностных температур Мирового океана. Виявлено умови, за яких статистичні зв'язки міжрічних змін сумарних тривалостей періодів переважання в Північній півкулі Землі Елементарних циркуляційних Механізмів, що відносяться за класифікацією Б. Л. Дзердіевского до груп Меридіональної Північної та меридіональної Південної, з варіаціями стану Арктичної осциляції, є значимими. Показано, що в сучасному періоді зміни характеристик цих зв'язків можуть бути обумовлені змінами розподілу поверхневих температур Світового океану.